SNP Variants at 16p13.11 Clarify the Role of the NDE1/miR-484 Locus in Major Mental Illness in Finland. Issue 1 (19th November 2020) - Sinha, Vishal; Ortega-Alonso, Alfredo; Ukkola-Vuoti, Liisa; Linnaranta, Outi; Zheutlin, Amanda B; Torniainen-Holm, Minna; Therman, Sebastian; Tuulio-Henriksson, Annamari; Jylhä, Pekka; Kaprio, Jaakko; Hovatta, Iiris; Isometsä, Erkki; et al.
Abstract: Through copy number variations, the 16p13.11 locus has been consistently linked to mental disorders. This locus contains the NDE1 gene, which also encodes microRNA-484. Both of them have been highlighted to play a role in the etiology of mental illness. A 4-SNP haplotype spanning this locus has been shown to associate with schizophrenia in Finnish females. Here we set out to identify any functional variations implicated by this haplotype. We used a sequencing and genotyping study design to identify variations of interest in a Finnish familial cohort ascertained for schizophrenia. We identified 295 variants through sequencing, none of which were located directly within microRNA-484. Two variants were observed to associate with schizophrenia in a sex-dependent manner (females only) in the whole schizophrenia familial cohort (rs2242549 P = .00044; OR = 1.20, 95% CI 1.03–1.40; rs881803 P = .00021; OR = 1.20, 95% CI 1.02–1.40). Both variants were followed up in additional psychiatric cohorts, with neuropsychological traits, and gene expression data, in order to further examine their role. Gene expression data from the familial schizophrenia cohort demonstrated a significant association between rs881803 and 1504 probes (FDR q < 0.05). These were significantly enriched for genes that are predicted miR-484 targets ( n = 54; P = .000193), and with probes differentially expressed between the sexes ( n = 48; P = .000187). While both SNPs are eQTLs for NDE1, rs881803 is located in a predicted transcription factor binding site. Based on its location and association pattern, we conclude that rs881803 is the prime functional candidate under this locus, affecting the roles of both NDE1 and miR-484 in psychiatric disorders.